Evolutionary economics and creative destruction - Metcalfe, J. S. (J. Stanley) (Graz Schumpeter lectures ;, 2002)
The central theme of this book is competition treated as an evolutionary process in which the focus is upon economic change and not economic equilibrium. This theme is explored by linking together differences in economic behaviour with the role of markets as co-ordinating institutions. In this picture innovation plays a central role as a primary source of differential behaviour of firms and the purpose of the book is to identify the consequences of these differences for competition and competitive advantage. -- Provided by publisher.